Oral squamous cell carcinoma in a patient with scimitar syndrome. Issue 1 (January 2018) - Sekido, Katsuhisa; Tomihara, Kei; Fujiwara, Kumiko; Tachinami, Hidetake; Imaue, Shuichi; Noguchi, Makoto
Abstract: Scimitar syndrome is a rare congenital cardiac condition with a poor prognosis. It is frequently accompanied by concordant pulmonary hypoplasia and aortopulmonary collateral arteries connected to the hypoplastic lung. Here we report a case involving a 58-year-old woman with scimitar syndrome who developed stage II oral cancer. Surgical treatment was deemed high risk because of difficulty in respiratory management through mechanical ventilation during general anesthesia, and hence, she was treated with chemoradiotherapy, which was successfully completed. The findings from this case suggest that chemoradiotherapy is a useful strategy that can contribute to improved clinical outcomes for oral cancer in patients with scimitar syndrome.